2020
DOI: 10.3389/fphys.2020.580223
|View full text |Cite
|
Sign up to set email alerts
|

Ficus carica L. Attenuates Denervated Skeletal Muscle Atrophy via PPARα/NF-κB Pathway

Abstract: Treatment options for denervated skeletal muscle atrophy are limited, in part because the underlying molecular mechanisms are not well understood. Unlike previous transcriptomics studies conducted in rodent models of peripheral nerve injury, in the present study, we performed high-throughput sequencing with denervated atrophic biceps muscle and normal (non-denervated) sternocleidomastoid muscle samples obtained from four brachial plexus injury (BPI) patients. We also investigated whether Ficus carica L. (FCL.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Loss of wet weight is one of the most intuitive representations of muscle atrophy [29,30]. Biological ndings in this study showed that the wet weight of rectus femoris muscles decreased with the prolonging of immobilization time.…”
Section: Discussionmentioning
confidence: 49%
“…Loss of wet weight is one of the most intuitive representations of muscle atrophy [29,30]. Biological ndings in this study showed that the wet weight of rectus femoris muscles decreased with the prolonging of immobilization time.…”
Section: Discussionmentioning
confidence: 49%
“…Previous basic and clinical studies have suggested that neutrophils are major participants in early inflammatory processes and can be swiftly deployed to sites of damage or infection [45][46][47] . However, to date, only a few inflammation-related molecules have been found in denervated muscle 48,49 . Although denervated muscle cells themselves are not directly harmed or infected and no local pathogens attract neutrophils during denervation, we demonstrated the dynamic changes in the number of neutrophils in the circulation and in muscle over time after denervation.…”
Section: Discussionmentioning
confidence: 99%
“…Although p53 signaling can respond to cell pressure and regulate autophagy, apoptosis, and the cell cycle to maintain cell homeostasis, dysfunctional p53 signaling is associated with a variety of diseases. Increased expression of p53 and its target genes has been previously observed in muscle atrophy models of aging [ 46 ], muscle denervation [ 47 ], and Huntington′s disease [ 48 ]. Therefore, we speculate that the starvation and oxidative stress induced by excessive exercise lead to ER pressure and activate p53 signaling.…”
Section: Discussionmentioning
confidence: 99%